Synthesis of Abscisic Acid in Neopyropia yezoensis and Its Regulation of Antioxidase Genes Expressions Under Hypersaline Stress - Yang, Jiali; Gu, Wenhui; Feng, Zezhong; Yu, Bin; Niu, Jianfeng; Wang, Guangce (Frontiers in Microbiology, 2022)
Abscisic acid (ABA) is regarded as crucial for plant adaptation to water-limited conditions and it functions evolutionarily conserved.. Thus, insights into the synthesis of ABA and its regulation on downstream stress-responsive genes in Neopyropia yezoensis, a typical Archaeplastida distributed in intertidal zone, will improve the knowledge about how ABA signaling evolved in plants. Here, the variations in ABA contents, antioxidant enzyme activities and expression of the target genes were determined under the presence of exogenous ABA and two specific inhibitors of the ABA precursor synthesis. ABA content was down-regulated under the treatments of each or the combination of the two inhibitors. Antioxidant enzyme activities like SOD, CAT and APX were decreased slightly with inhibitors, but up-regulated when the addition of exogenous ABA. The qRT-PCR results were consistent with the enzyme activities. All the results suggested that ABA can also alleviate oxidative stress in N. yezoensis as it in terrestrial plant. Combined with the transcriptome assay, it was hypothesized that ABA is synthesized in N. yezoensis via a pathway that is similar to the carotenoid pathway in higher plants, and both the MVA and that the MEP pathways for IPP synthesis exist simultaneously. The ABA signaling pathway in N. yezoensis was also analyzed from an evolutionary standpoint and it was illustrated that the emergence of the ABA signaling pathway in this alga is an ancestral one. In addition, the presence of the ABRE motif in the promoter region of antioxidase genes suggested that the antioxidase system is regulated by the ABA signaling pathway.